Effectiveness of an Educational Program on Nurses’ Knowledge about Communicable Diseases Control in Al-Nassiriyah City Hospitals (Medico Legal Update, 2021)
Communicable diseases are an illness that is transmitted from a person, animal, or inanimate source toanother person either directly, with the assistance of a vector or by other means. Communicable diseases area major cause of mortality and morbidity in emergencies, and particularly in complex emergencies, wherecollapsing health services and disease control programs. They are the basic level of infectious pathogenscontrol precautions which are to be used, as a minimum, in the care of all patients. A quasi-experimentaldesign (descriptive study) used to guide this study; it was applied by use of pretest-posttest approach for twogroups of samples (study and control) Non- probability (purposive) sample of (80) nurses who are workingin Al-Nasiriyah city hospitals.The findings of the current study revealed that there are highly statistically significant differences in posttest.The study concludes that there is poor and low level of knowledge assessment among the participants towardcommunicable diseases control at the pre-test in the both group. The results show after the implementationof educational program high level of nurses’ knowledge for (post-test I and post-test II) for the study groupregarding communicable diseases control. The study concludes there were no significant association betweennurses’ knowledge and their socio demographic characteristics includes: age; gender; level of education andyears of experience. The study recommends of the providing an educational and training program periodicallyfor nurses in order to enhancement the level of their knowledge regarding communicable diseases control.